Microplastics in commercial clams from the intertidal zone of the South Yellow Sea, China - Tang, Ruikai; Zhang, Tao; Song, Kexin; Sun, Yixin; Chen, Yangjun; Huang, Wei; Feng, Zhihua (Frontiers in Marine Science, 2022)
Clams are commercially important species and are a vital component of the offshore ecosystem. Investigations on microplastics (MPs) in clams have attracted public attention recently, for its ecological and food safety risks. However, knowledge gaps still exist regarding MPs in commercial clams from the intertidal zone of the South Yellow Sea (SYS), China, an important clam habitat. In this study, to investigate the distribution of MPs in clams of the SYS, four species of clams were collected from nine sites in different tide zones (high, middle, and low tides) in three coastal areas (Nantong, Yancheng and Lianyungang). The abundance and characteristics of MPs, including size, shape, color and composition, were determined using microscope and micro-Fourier transform infrared (FTIR) spectroscopy. Furthermore, to evaluate the MPs purification ability of clams, the abundance of MPs in various tissues was examined by microscopic observation after being purified in filtered seawater for 72 h. The results showed that there were significant differences in the abundance of MPs in clams from different regions, with the most serious pollution in the high-tide zone. Moreover, the lowest MPs abundance was found in Yancheng (5.07 ± 2.73 items/individual, 1.16 ± 0.78 items/g), while Lianyungang was found with the most abundant MPs (7.52 ± 2.68 items/individual, 3.94 ± 3.00 items/g). The size of MPs in Ruditapes philippinarum (1,329.99 μm) was significantly higher than in other species. The MPs in clams were characterized by fiber in shape, black-grey, blue-green and white-transparent in color and rayon in composition. Moreover, it was found that the MPs originally present in various tissues tended to migrate and accumulate into the mantle of the clam during depuration, and after 72 h of depuration, removing the mantle could reduce nearly half amount of microplastics in clams. Overall, our study revealed the microplastic distribution in commercial clams from the intertidal zone of the SYS and provided suggestions for the safety of aquatic production.